Associations between exposure to volatile organic compounds with obesity in adults - Runmiao Wu; Lei Jia; Xu Zhu; Gongchang Guan; Junkui Wang; Rutai Hui; Meijuan Ma; Zhao Zhao; Hui Pang; Ling Zhu (Human Nutrition & Metabolism, 2025)
Objective: This study was to investigate the correlation between urine volatile organic compound (VOC) metabolites and obesity-related outcomes, including BMI, waist circumference, obesity, and abdominal obesity. Methods: Data from the National Health and Nutrition Examination Survey (NHANES) conducted between 2011 and 2016 were utilized for this analysis. Linear regression and logistic regression models were employed to estimate β-coefficients or odds ratios (ORs) along with their corresponding 95 % confidence intervals (CIs). Quantile g-computation (Qgcomp) regression, a method designed to evaluate the combined effects of multiple correlated chemical exposures, was used to assess the mixed influence of VOC metabolites on obesity-related outcomes. Results: A total of 4950 adults were included in this analysis. The median age of the participants was 47 (33, 60) years, with 49.3 % being male. The median BMI was 27.7 (24.2, 32.4) kg/m2, and the median waist circumference was 98.0 (87.3, 109.0) cm. The prevalence of obesity and abdominal obesity was 36.8 % and 56.5 %, respectively. After adjusting for all covariates, urine VOC metabolites (including AAMA, AMCC, BMA, CYMA, DHBMA, 3HPMA, 2HPMA, MA, 2MHA, 3MHA+4MHA, MHBMA3, PGA, and HPMMA) exhibited a negative association with obesity. With the exception of BMA and DHBMA, similar results were observed regarding the association between urine VOC metabolites and the prevalence of abdominal obesity. Additionally, Qgcomp regression analysis revealed a significant negative correlation between the mixture of urine VOC metabolites and all obesity-related outcomes, with 2HPMA demonstrating the strongest influence on this negative association. Conclusion: Our findings suggest a negative relationship between exposure to VOCs, as measured by urine VOC metabolite levels, and obesity in adults.